Tissue Dependent Role of PTX3 During Ischemia-Reperfusion Injury - de Oliveira, Thiago Henrique Caldeira; Souza, Danielle G.; Teixeira, Mauro Martins; Amaral, Flávio Almeida (Frontiers in Immunology, 2019)
Reperfusion of an ischemic tissue is the treatment of choice for several diseases, including myocardial infarction and stroke. However, reperfusion of an ischemic tissue causes injury, known as Ischemia and Reperfusion Injury (IRI), that limits the benefit of blood flow restoration. IRI also occurs during solid organ transplantation. During IRI, there is activation of the innate immune system, especially neutrophils, which contributes to the degree of injury. It has been shown that PTX3 can regulate multiple aspects of innate immunity and tissue inflammation during sterile injury, as observed during IRI. In humans, levels of PTX3 increase in blood and elevated levels associate with extent of IRI. In mice, there is also enhanced expression of PTX3 in tissues and plasma after IRI. In general, absence of PTX3, as seen in PTX3-deficient mice, results in worse outcome after IRI. On the contrary, increased expression of PTX3, as seen in PTX3 transgenic mice and after PTX3 administration, is associated with better outcome after IRI. The exception is the gut where PTX3 seems to have a clear deleterious role. Here, we discuss mechanisms by which PTX3 contributes to IRI and the potential of taming this system for the treatment of injuries associated with reperfusion of solid organs.